2012
DOI: 10.1099/jmm.0.049817-0
|View full text |Cite
|
Sign up to set email alerts
|

Trichosporon asahii causing nosocomial urinary tract infections in intensive care unit patients: genotypes, virulence factors and antifungal susceptibility testing

Abstract: Trichosporon asahii is the causative agent of both superficial and deep-seated infections of increasing morbidity and mortality. Urinary tract infections (UTIs) due to T. asahii, frequently associated with indwelling medical devices, have been reported over the years. However, few studies have specifically focused on the genotypic diversity of T. asahii isolates from urine specimens from intensive care units (ICUs), let alone potential virulence factors and antifungal susceptibility testing. In the present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 44 publications
3
51
1
3
Order By: Relevance
“…Biofilms produced by Trichosporon spp. also presented higher tolerance to antifungals (Di Bonaventura et al, 2006;Iturrieta-González et al, 2014;Liao et al, 2014;Sun et al, 2012). Data from the present study reveal that planktonic cells showed susceptibility to azoles and resistance to amphotericin B and caspofungin.…”
supporting
confidence: 52%
See 2 more Smart Citations
“…Biofilms produced by Trichosporon spp. also presented higher tolerance to antifungals (Di Bonaventura et al, 2006;Iturrieta-González et al, 2014;Liao et al, 2014;Sun et al, 2012). Data from the present study reveal that planktonic cells showed susceptibility to azoles and resistance to amphotericin B and caspofungin.…”
supporting
confidence: 52%
“…Liao et al (2015) tested ethanol efficacy against T. asahii biofilms in three different adhesion times, at 30 min, 1 and 2 h, with a starter inoculum of 10 6 cells ml 21 in RPMI medium. Sun et al (2012) evaluated the same adhesion times, at 30 min, 1 and 2 h, in T. asahii biofilms, with a starter inoculum of 10 5 cells ml…”
Section: Semmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study by Wei sun, et al, though diabetes was the most common risk factor the percentage reported was little less i.e. 34.7% [28]. This difference may be due to the variations in the prevalence of diabetes mellitus in different geographical regions.…”
Section: Discussionmentioning
confidence: 94%
“…In the recent years other fungi emerged as important infections agents, including yeast species such as non-albicans Candida species, Cryptococcus sp., Trichosporon spp., and Rhodotorula spp. and filamentous fungi such as Fusarium spp., Rhizopus spp., Rhizomucor spp., and phaeohyphomycosis agents (Sun et al, 2012;Juyal et al, 2013;Kim et al, 2013;Muhammed et al, 2013;Jaın et al, 2014;Schieffelin et al, 2014).…”
Section: Fungus: Overall Look In the Main Topicmentioning
confidence: 99%